The responsibility of the media in the institutional consolidation of the Modern Democratic State - Borea Odría, Alberto (2015)
What role does the media fulfill in the current stage of Latin American democracy? In all cases, is the possibility of regulating the media incompatiblewith the freedom of speech and enterprise of thepeople who own it?In this article, the renowned author shows his point of view regarding these questions, as well as offering a critique related to how the relationship between the media and democracy has been developing in our society. Lastly, he presents a proposal of media regulation in order to make democracy viable, but without   compromising constitutional freedoms.